Barriers and benefits to the adoption of a third party certified food safety management system in the food processing sector in Shanghai, China - Qijun, J.; Batt, Peter (Pergamon, 2016)
Despite the recent passing of legislation by the National People's Congress of China in 2009, many food businesses in China have yet to implement a third party certified food safety management system (FSMS). While the extent literature identifies a number of internal and external barriers and benefits, the extent to which these impact on the business is thought to be dependent upon how much progress the firm has made on its journey towards quality assurance and the environment within which the firm operates. To test this proposition, the barriers and the benefits accrued from the implementation of a third party certified FSMS were explored by segregating the participating firms into three distinct groups; (i) those that have yet to implement a third party certified FSMS; (ii) those that were in the process of adopting a third party certified FSMS; and (iii) those that were already operating under a third party certified FSMS. Contrary to expectations, in what is a highly competitive market, those firms which were operating under a third party certified FSMS were more likely to question the benefits they had derived than those firms that were either in the process of adoption or had chosen not to adopt a third party certified FSMS. Irrespective of the stage of adoption, the major constraint to the implementation of a third party certified FSMS was the need for the organisation to focus on more immediate issues and the lack of any strategic long-term planning.